Al-Mn series aluminum alloy and preparation method and application thereof

By introducing AlxCuy nanostrengthening phase and AlMnFeSi diffuse phase into Al-Mn-type aluminum alloy, combined with a specific annealing process, the problem of difficulty in taking into account the strength and plasticity of Al-Mn-type aluminum alloy is solved, and high yield strength and elongation are achieved Take into account and reduce processing time and energy consumption.

CN119144876APending Publication Date: 2024-12-17HUAFENG ALUMINUM CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411157593.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing Al-Mn-type aluminum alloys are difficult to maintain the plasticity of the material while increasing the strength, especially through deformation strengthening and solid solution strengthening, which will lead to a decrease in elongation, and the existing processes are time-consuming and energy-consuming.

Method used

The synergistic effect of the AlxCuy nanostrengthening phase and the AlMnFeSi diffuse phase is adopted to control the solid solubility of Mn and the content of Cu, Mg, and Si, and combine with a specific annealing process to form an Al-Mn-based aluminum alloy with high yield strength and elongation.

Benefits of technology

The high yield strength (greater than 60MPa) and elongation (greater than 15%) of Al-Mn-based aluminum alloy is achieved, avoiding the problem of reducing material plasticity in traditional processes, and reducing processing time and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144876A_ABST
    Figure CN119144876A_ABST
Patent Text Reader

Abstract

The invention provides an Al-Mn series aluminum alloy as well as a preparation method and application thereof. The Al-Mn series aluminum alloy contains an Al < x > Cu < y > nano strengthening phase and an Al Fe < Si > dispersed phase, the solid solubility of Mn in the Al-Mn alloy is less than or equal to 0.4 wt%; and the atomic number ratio x: y of Al to Cu in the Al < x > Cu < y > nano strengthening phase is 2: 1-4: 1. The preparation method comprises the following steps: (1) burdening according to the components and the weight percentage to obtain a mixed material; (2) smelting and casting the mixed material prepared in the step (1) in sequence to obtain an aluminum ingot; (3) the aluminum ingot obtained in the step (2) is subjected to homogenization treatment for 8-15 h at the temperature of 500-600 DEG C, an AlMnSiFe phase is separated out, and a homogenized sample is obtained; and (4) the homogenized sample obtained in the step (3) is sequentially subjected to first hot rolling, cold rolling, first annealing, second hot rolling and second annealing, so that an AlxCuy nanometer strengthening phase is formed, and the Al-Mn series aluminum alloy is obtained. The Al-Mn series aluminum alloy provided by the invention is excellent in plasticity, high in strength and wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an Al-Mn aluminum alloy and a preparation method and application thereof. Background Art

[0002] Aluminum alloys have low density, high specific strength, good lightness and heat dissipation performance, as well as excellent cutting and casting performance. They are widely used in aerospace, transportation, shipbuilding, construction and other fields. Among them, Al-Mn series aluminum alloys have good thermal conductivity, strength, rust resistance, corrosion resistance and processing performance, so they are widely used in the field of heat transfer. The existing alloy scheme is Mn: 1.0-1.5wt%, Si: 0.3-0.6wt%, Fe: 0.5-0.8wt%, Cu: 0.05-0.2wt%. The main strengthening methods are solid solution strengthening and dispersion strengthening. After full annealing, its yield strength is generally 35-50MPa, the tensile strength is 95-135MPa, and the elongation is 17-25%.

[0003] However, most aluminum alloy materials currently used in the field of heat transfer are often only used as functional parts. With the demand for low-carbon environmental protection and lightweight development, the manufacturing industry urgently needs aluminum alloy materials with certain structural functions. Therefore, the strength requirements for heat transfer materials are increasing. In addition, considering that most aluminum heat transfer materials are formed by stamping and inflation, there are also high requirements for the plasticity of the material. However, most strengthening methods will lead to a decrease in the plasticity of the material, especially deformation strengthening and solid solution strengthening will greatly reduce the elongation of the material.

[0004] CN116875864B discloses that by adding Mg and Si elements, nano-sized Mg2Si precipitate phase can be precipitated during the aging process to strengthen the material, and the adverse effect on plasticity is also small. However, such materials need to be heated to 500-610°C in advance for solution treatment, and then need to be heated to 170-250°C for 30min-12h for artificial aging or placed at room temperature for 1-2 weeks for natural aging. The maximum strength can only be achieved after the aging is completed, which consumes energy and wastes time. However, the tensile strength of the Al-Mn aluminum alloy plate material obtained by improving the process by relying solely on dispersed phase strengthening is limited.

[0005] Based on the above, it is urgent to develop an Al-Mn alloy material with excellent strength and elongation for use in the field of heat transfer. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides an Al-Mn aluminum alloy and a preparation method and use thereof, which solves the problem that it is difficult to balance the strength and plasticity of existing Al-Mn aluminum alloys, and provides an Al-Mn alloy material that can be used in the field of heat transfer and has excellent strength and elongation.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an Al-Mn aluminum alloy, wherein the Al-Mn aluminum alloy contains Al x Cu y Nano-strengthening phase and AlMnFeSi dispersed phase;

[0009] The solid solubility of Mn in the Al-Mn aluminum alloy is ≤0.4wt%;

[0010] The Al x Cu y The atomic number ratio x:y of Al and Cu elements in the nano-strengthening phase is 2:1 to 4:1.

[0011] The Al-Mn aluminum alloy of the present invention is mainly composed of Al x Cu y Strengthening in the form of nano-reinforced phase and AlMnFeSi dispersed phase precipitation makes the material have high strength and plasticity. The strengthening effect of Mn element in the alloy mainly includes solid solution strengthening and dispersion strengthening. Although the solid solution strengthening of Mn can effectively improve the yield strength, it has a significant effect on the elongation of the material. When the solid solubility of Mn is greater than 0.4wt%, the elongation of the material will exceed the acceptable range. Therefore, it is necessary to control the solid solubility of the Mn element in the system so that Mn is more strengthened by precipitation of AlMnFeSi dispersed phase. The solid solubility of Mn is ≤0.4wt%, for example, it can be 0.4wt%, 0.3wt%, 0.2wt% or 0.1wt%, etc.

[0012] The Al of the present invention x Cu y Compared with the Al2Cu phase formed in the conventional 2XXX aluminum alloy with high Cu content, the Al:Cu ratio of the nano-strengthened phase is different, and the x:y is 2:1-4:1. x Cu y The nano-reinforced phase significantly improves the strength level of the original Al-Mn alloy.

[0013] Among them, x:y is 2:1 to 4:1, for example, it can be 2:1, 2.1:1, 2.3:1, 2.5:1, 2.8:1, 2.9:1, 3.0:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.8:1 or 4:1, etc.

[0014] Preferably, the Al-Mn aluminum alloy has a phase size of ≤70 nm. x Cu y The area proportion of nano-strengthening phase is ≥1.1%, and there is basically no Al larger than 70nm in the system. x Cu y Nano-reinforced phase exists.

[0015] The phase size is ≤70nm, for example, it can be 50nm, 53nm, 55nm, 57nm, 59nm, 62nm, 64nm, 66nm, 68nm or 70nm. x Cu y The area proportion of the nano-reinforced phase is ≥ 1.1%, for example, it may be 1.1%, 1.2%, 1.3%, 1.4%, 2.2%, etc.

[0016] Preferably, the composition of the Al-Mn aluminum alloy includes, by mass percentage, 0.3-0.6% Mg and 0.5-1.0% Cu.

[0017] Among them, 0.3-0.6% Mg can be, for example, 0.3%, 0.34%, 0.37%, 0.4%, 0.44%, 0.47%, 0.5%, 0.54%, 0.57% or 0.6%, and 0.5-1.0% Cu can be, for example, 0.5%, 0.56%, 0.62%, 0.67%, 0.73%, 0.78%, 0.84%, 0.89%, 0.95% or 1.0%, etc.

[0018] The Al-Mn alloy of the present invention includes 0.3% to 0.6% of Mg element. The Mg element has a solid solution strengthening effect. More importantly, the Mg element can combine with Al and Cu elements to form an unstable submicron-sized AlCuMg phase. In the subsequent specific annealing process, the Mg element in the AlCuMg phase is dissolved back into the Al matrix, thereby forming Al x Cu y Nano-strengthening phase. When the Mg content is lower than 0.3%, the AlCuMg phase is affected. When the Mg content is higher than 0.6%, part of the Mg element will be dissolved in the matrix during the entire material processing process. It is difficult to completely dissolve the Mg element in the AlCuMg phase in the matrix during the secondary annealing process, resulting in a large amount of residual AlCuMg phase and Al x Cu y The reduction of the distribution density of the nano-reinforced phase leads to a reduction in the strengthening effect.

[0019] The Al-Mn alloy of the present invention includes 0.5% to 1.0% Cu element, which mainly plays the role of solid solution strengthening and precipitation strengthening. Through experimental research, it is found that when the Cu content is lower than 0.5%, it is difficult to produce Al in the subsequent annealing process. x Cu y Nano-strengthening phase results in no significant strengthening improvement; when the Cu content is higher than 1.0%, the plasticity of the aluminum alloy will be significantly reduced.

[0020] Preferably, the phase size of the AlMnFeSi dispersed phase is ≤650nm, there are substantially no AlMnFeSi dispersed phase particles larger than 650nm in the aluminum alloy structure, and the area proportion of the AlMnFeSi dispersed phase is ≥1.4%.

[0021] The phase size is ≤650nm, for example, it can be 40nm, 108nm, 176nm, 244nm, 312nm, 379nm, 447nm, 515nm, 583nm or 650nm, and the area ratio is ≥1.4%, for example, it can be 1.4%, 1.6%, 1.9%, 2.3%, 2.6% or 2.9%, etc.

[0022] Preferably, the composition of the Al-Mn aluminum alloy includes, by mass percentage, 0.6-1.5% Mn, 0.2-0.5% Fe and 0.5-1.0% Si.

[0023] Among them, 0.6-1.5% Mn can be, for example, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, 0.2-0.5% Fe can be, for example, 0.2%, 0.24%, 0.27%, 0.3%, 0.34%, 0.37%, 0.4%, 0.44%, 0.47% or 0.5%, and 0.5-1.0% Si can be, for example, 0.5%, 0.56%, 0.62%, 0.67%, 0.73%, 0.78%, 0.84%, 0.89%, 0.95% or 1.0%, etc.

[0024] The Al-Mn alloy of the present invention includes 0.6% to 1.5% of Mn element, and the Mn element mainly plays the role of solid solution strengthening and dispersion strengthening. When the Mn element content in the aluminum alloy is lower than 0.6%, the solid solution strengthening effect is small, and it is difficult to ensure that sufficient submicron-sized AlMnFeSi dispersed phases are precipitated during the subsequent heat treatment process. The AlMnFeSi dispersed phase can hinder the movement of dislocations and play the role of dispersion strengthening. When the Mn content is higher than 1.5%, it is easy to cause the Mn element and other elements to produce coarse intermetallic compounds during the casting process, which will have an adverse effect on the mechanical properties of the aluminum alloy material.

[0025] The Al-Mn alloy also contains 0.2% to 0.5% of Fe element, wherein the content of Fe+Mn should be ≤1.9%, otherwise coarse Al6 (FeMn) phase will be produced, which will seriously weaken the mechanical properties of the aluminum alloy.

[0026] The Al-Mn alloy also contains 0.5% to 1.0% Si element. On the one hand, the Si element can improve the fluidity of the alloy during the casting process. On the other hand, the Si element can also play a role in solid solution strengthening.

[0027] Preferably, the content of Fe+Mn in the Al-Mn aluminum alloy is ≤1.9%, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7% or 1.8%.

[0028] Preferably, the average grain size of the Al—Mn aluminum alloy is ≤24 μm, for example, it may be 1 μm, 3 μm, 4 μm, 6 μm, 7 μm, 9 μm, 12 μm, 15 μm, 21 μm or 24 μm.

[0029] The present invention controls the average grain size of the structure to be ≤24 μm by means of a grain refinement method, and more preferably, controls it to be ≤14 μm, which is more conducive to obtaining high strength.

[0030] Preferably, the Al-Mn aluminum alloy further comprises 0.01% to 0.1% Ti, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.1%, etc. In the present invention, 0.01% to 0.1% Ti element mainly plays a role in refining grains.

[0031] In a second aspect, the present invention provides a method for preparing the Al-Mn aluminum alloy according to the first aspect, the preparation method comprising the following steps:

[0032] (1) preparing ingredients according to components and weight percentages to obtain a mixed material;

[0033] (2) melting and casting the mixed material prepared in step (1) in sequence to obtain an aluminum ingot;

[0034] (3) homogenizing the aluminum ingot obtained in step (2) at 500-600° C. for 8-15 h to precipitate an AlMnSiFe phase, thereby obtaining a homogenized sample;

[0035] (4) The homogenized sample in step (3) is subjected to first hot rolling, cold rolling, first annealing, second hot rolling and second annealing in sequence to form Al x Cu y Nano-strengthening phase is obtained to obtain the Al-Mn aluminum alloy.

[0036] The purpose of homogenization in the present invention is to prevent excessive Mn elements from being dissolved in the matrix. An increase in the amount of Mn elements dissolved in the matrix will lead to higher strength of the material, but a significant decrease in elongation.

[0037] The temperature of the homogenization treatment is 500-600°C, for example, it can be 500°C, 512°C, 523°C, 534°C, 545°C, 556°C, 567°C, 578°C, 589°C or 600°C, etc.; the time is 8-15h, for example, it can be 8h, 8.8h, 9.6h, 10.4h, 11.2h, 11.9h, 12.7h, 13.5h, 14.3h or 15h, etc. The homogenization temperature should not be lower than 500°C. Too low homogenization temperature will cause a large amount of Mn element to be dissolved in the matrix. Although it will improve the strength of the material to a certain extent, it will have a greater negative impact on the elongation of the material, causing the plasticity of the material to deteriorate seriously and making it difficult to use; the homogenization temperature should not exceed 600°C, otherwise the homogenization temperature will be close to the melting point of the aluminum alloy, which will make it impossible to process.

[0038] It is worth noting that the inventors found that Al x Cu y Nano-strengthening phase is beneficial to improving the strength of aluminum alloy materials. Al2Cu phase can be obtained in existing aluminum alloys with high Cu content. However, the elongation of the well-known 2XXX series Al-Cu alloys is low, which leads to poor plasticity of such materials. If a large amount of Cu element is introduced into the 3XXX series Al-Mn alloy to improve the strength, the Al-Mn alloy will lose its plasticity. If the Cu content is reduced to 1%, it will have little effect on the plasticity of the Al-Mn alloy, but it will also lead to the inability to obtain Al2Cu strengthening phase. The inventor can obtain Al in the alloy containing both Mg and Cu. x Cu y Nano-strengthening phase, Mg element can combine with Al and Cu elements to form unstable submicron-sized AlCuMg phase. In the subsequent specific annealing process, the Mg element in the AlCuMg phase is dissolved back into the Al matrix, thus forming Al x Cu y Nano-strengthening phase. Al x Cu y Compared with the Al2Cu phase obtained by conventional 2XXX, the Al:Cu ratio of the nano-reinforced phase is different, and the x:y is 2:1-4:1. x Cu y The nano-reinforced phase significantly improves the strength level of the original Al-Mn alloy.

[0039] Preferably, refining, impurity removal and degassing are performed during the smelting process.

[0040] Preferably, the homogenization process is preceded by a peeling process.

[0041] Preferably, the temperature of the homogenization treatment in step (3) is 590° C. and the time is 9 hours.

[0042] Preferably, after the homogenization treatment, the aluminum ingot is placed in air to cool to room temperature.

[0043] Preferably, the temperature of the first annealing is 300-360°C, for example, 300°C, 307°C, 314°C, 320°C, 327°C, 334°C, 340°C, 347°C, 354°C or 360°C, etc., and the time is 1-3h, for example, 1h, 1.3h, 1.5h, 1.7h, 1.9h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, etc. Preferably, the temperature of the first annealing is 350°C, and the time is 3h.

[0044] The present invention performs annealing at 300-360°C for 1-3h, so that the aluminum alloy undergoes sufficient recrystallization, refines the grains, and at the same time, promotes the precipitation of submicron-sized AlMgCu phases in the matrix. If the first annealing temperature is too high, the particle size of the precipitated phase (AlMgCu phase and AlMnFeSi dispersed phase) will be too large, and long-term high-temperature annealing will cause grain coarsening; if the first annealing temperature is too low, less submicron-sized AlMgCu phases will be precipitated.

[0045] Preferably, the second annealing temperature is 455-465°C, for example, 455°C, 457°C, 458°C, 459°C, 460°C, 461°C, 462°C, 463°C, 464°C or 465°C, and the time is 20-60 min.

[0046] The second annealing is performed at a temperature of at least 455°C because the solid solubility of Mg in the Al matrix is ​​relatively large at this temperature, which is conducive to dissolving the Mg element in the AlMgCu phase into the matrix, thereby forming Al x Cu y For nano-strengthening phase, the annealing time should not be too long mainly to prevent grain coarsening.

[0047] When the second annealing temperature is higher than 465℃, it will lead to coarse grains and excessively large precipitate particles. x Cu y The sizes of nano-reinforced phase and AlMnFeSi dispersed phase both exceeded the target values.

[0048] Preferably, the preheating temperature of the first hot rolling is 450-500°C, for example, 450°C, 456°C, 462°C, 467°C, 473°C, 478°C, 484°C, 489°C, 495°C or 500°C. The preheating time of the first hot rolling is 1-2h, for example, 1h, 1.2h, 1.5h, 1.7h, 2h, etc. The thickness after the first hot rolling is 5-8mm, for example, 5mm, 5.4mm, 5.7mm, 6mm, 6.4mm, 6.7mm, 7mm, 7.4mm, 7.7mm or 8mm, etc. Preferably, the preheating temperature of the first hot rolling is 480°C, the preheating time of the first hot rolling is 1.5h, and the thickness after the first hot rolling is 6mm.

[0049] Preferably, the thickness after cold rolling is 2 to 4 mm, for example, it can be 2 mm, 2.3 mm, 2.5 mm, 2.7 mm, 2.9 mm, 3.2 mm, 3.4 mm, 3.6 mm, 3.8 mm or 4 mm, etc., preferably 3 mm.

[0050] Preferably, the preheating temperature of the second hot rolling is 475-485°C, for example, it can be 475°C, 477°C, 478°C, 479°C, 480°C, 481°C, 482°C, 483°C, 484°C or 485°C, and the thickness after the second hot rolling is 1-2mm, for example, it can be 1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm or 2mm, etc. Preferably, the preheating temperature of the second hot rolling is 480°C, and the thickness after the second hot rolling is 1.5mm.

[0051] Preferably, the preheating time of the second hot rolling is 20 to 40 min, for example, it can be 20 min, 23 min, 25 min, 28 min, 30 min, 33 min, 35 min, 38 min or 40 min.

[0052] The present invention further preferably controls the preheating temperature before the second hot rolling to 475-485°C, which can be coordinated with the second annealing to effectively dissolve the Mg element in the AlMgCu phase back into the Al matrix, thereby precipitating Al x Cu y The nano-reinforced phase accounts for a larger area.

[0053] The present invention is based on Al-Mn alloy widely used in the field of heat transfer, and prepares an AlMn alloy with high yield strength by adding strengthening elements such as Cu, Mg, and Si, and adjusting the ratio of Mg and Cu elements and the processing technology. The AlMn alloy with high yield strength not only precipitates the conventional AlMnSiFe dispersed phase, but also precipitates smaller AlMnSiFe dispersed phase by adjusting the processing technology. xCu y The nano-reinforced phase effectively improves the yield strength of the material without significantly reducing the elongation of the material.

[0054] In a third aspect, the present invention provides a use of the Al-Mn aluminum alloy described in the first aspect in the field of heat transmission.

[0055] Compared with the prior art, the present invention has at least the following beneficial effects:

[0056] (1) The Al-Mn aluminum alloy provided by the present invention makes full use of the solid solution strengthening of Mn, Cu, and Mg elements, the dispersion strengthening of submicron-sized AlMnSiFe phases, and the nano-sized Al x Cu y The synergistic effect of precipitation strengthening of the nano-strengthening phase effectively improves the yield strength of the AlMn alloy. The yield strength of the invented material is greater than 60MPa and the elongation is greater than 15%;

[0057] (2) The preparation method of the Al-Mn aluminum alloy provided by the present invention is to homogenize the Al-Mn aluminum alloy at 500-600°C for 8-15 hours, so that the Mn element dissolved in the Al matrix can be precipitated as a nano-sized AlMnSiFe phase, and the Cu and Mg elements can be fully dissolved in the Al matrix;

[0058] (3) The preparation method of the Al-Mn aluminum alloy provided by the present invention adopts a processing flow of first hot rolling, cold rolling, first annealing, second hot rolling and second annealing, wherein the first annealing can precipitate the Cu and Mg elements dissolved in the Al matrix in the form of nano-sized AlMgCu phase, and the second annealing can effectively dissolve the Mg element in the AlMgCu phase back into the Al matrix, thereby precipitating smaller Al x Cu y Nano-reinforced phase;

[0059] (4) The preparation method of the Al-Mn aluminum alloy provided by the present invention preferably performs a preheating treatment before the second hot rolling, which can cooperate with the second annealing to effectively dissolve the Mg element in the AlMgCu phase back into the Al matrix, thereby precipitating smaller Al x Cu y Nano-reinforced phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a diagram showing the distribution of the AlMnSiFe dispersed phase in the Al-Mn aluminum alloy provided in Example 1 of the present invention.

[0061] Figure 2 Al in the Al-Mn aluminum alloy provided in Example 1 of the present invention x Cuy Distribution diagram of nano-reinforced phase. DETAILED DESCRIPTION

[0062] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0063] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0064] General Definitions and Terms

[0065] When all technical terms used in this document conflict with the meanings commonly understood by ordinary technicians in the field to which the present invention belongs, the definitions in this specification shall prevail.

[0066] Unless otherwise indicated, all percentages, parts, ratios, etc., are by weight.

[0067] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper numerical limit and a preferred lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of range upper limits or preferred numerical values ​​with any range lower limits or preferred numerical values, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical ranges listed herein are intended to include the endpoints of the range, and all integers and fractions within the range. For example, "1-8" covers 1, 2, 3, 4, 5, 6, 7, 8 and any range consisting of any two values ​​therein, such as 2-6, 3-5.

[0068] The expression "comprising" or its synonymous similar expressions "including", "containing" and "having" etc. are open-ended and do not exclude additional unrecited elements, steps or ingredients. The expression "consisting of excludes any element, step or ingredient not specified. The expression "consisting essentially of means that the scope is limited to the specified elements, steps or ingredients, plus the optional elements, steps or ingredients that do not materially affect the basic and novel characteristics of the claimed subject matter. It should be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".

[0069] The term "atomic number ratio" refers to the ratio of the mass of each element in the precipitated phase divided by the relative atomic mass of the element.

[0070] Test method:

[0071] 1. Determination of phase size and atomic number ratio: After the prepared high yield strength Al-Mn alloy was cut into 15mm×15mm size, it was polished and thinned with 400 mesh, 800 mesh, 1200 mesh, and 2400 mesh sandpaper in turn, and the final thickness was 70-100nm; then the sample was punched into a projection sample with a diameter of 3mm using a wafer puncher; then the transmission sample was electrolytically double-sprayed in a solution of 30vol% nitric acid + 70vol% methanol to complete the preparation of the transmission sample; TEC produced by FEI of the United States was used A NAL transmission electron microscope was used at a voltage of 200KV and a magnification of 2500 to 20000 to observe the type and distribution of the precipitated phases. At the same time, EDS was used to test the composition of the precipitated phases and calculate the atomic number ratio of the precipitated phases. Imageproplus6.0 software developed by MEDIACYBERNETICS Image Technology Company of the United States was used to count the size and area ratio of the precipitated phases in the TEM photos. The statistically obtained phase size and area ratio are the average values ​​of at least three regions.

[0072] 2. Measurement of element content: The chemical composition of the prepared AlMn alloy was tested using a spectrometer.

[0073] 3. Method for measuring element solid solubility: Using a Zeiss Sigma300 field emission electron microscope, at a magnification of 5000 to 10000, at least three Al matrix areas without a second phase were subjected to surface scanning analysis, and the average value of each element content was calculated to obtain the solid solubility of each element in the matrix.

[0074] 4. Grain size measurement: After the Al-Mn alloy sheet is cut into samples of 20 mm × 10 mm in size, the longitudinal section of the sample is used as the observation surface during inlaying, and then grinding, polishing and vibration polishing are performed in sequence to obtain a metallographic sample. Then, an EBSD test is performed using a Zeiss Sigma300 field emission electron microscope equipped with an EBSD probe. After the test is completed, the AztecCrystal software is used for data processing, and its built-in data processing system is used to obtain the average grain size.

[0075] 5. Yield strength, tensile strength and elongation: The method disclosed in GB / T228.1-2010 "Tensile test of metal materials Part 1: Room temperature test method" was used to test the mechanical properties of the prepared medium-high strength aluminum alloy composite plate and the medium-high strength aluminum alloy composite plate after simulated brazing and aging treatment. The testing instrument was a ZWICK universal material testing machine. The tested indicators include yield strength, tensile strength and elongation, which refer to the plastic extension strength (Rp0.2), tensile strength (Rm) and elongation after fracture (A50) in the test method, and are usually called yield strength, tensile strength and elongation in the industry.

[0076] The compositions of the Al-Mn aluminum alloys provided in Examples 1-7 are shown in Table 1.

[0077] Table 1

[0078]

[0079]

[0080] The preparation method of the Al-Mn aluminum alloy provided in Examples 1-7 comprises the following steps:

[0081] (1) preparing ingredients according to components and weight percentages to obtain a mixed material;

[0082] (2) melting and casting the mixed material prepared in step (1) in sequence to obtain an aluminum ingot;

[0083] (3) homogenizing the aluminum ingot obtained in step (2) to obtain a homogenized sample;

[0084] (4) The homogenized sample in step (3) is subjected to a first hot rolling, a cold rolling, a first annealing, a second hot rolling and a second annealing in sequence to obtain the Al-Mn aluminum alloy.

[0085] The specific process parameters in the preparation methods of Examples 1-7 are shown in Table 2.

[0086] Table 2

[0087] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Homogenization temperature / ℃ 590 500 600 590 590 590 600 Homogenization time / h 9 15 8 9 9 9 8 First hot rolling preheating temperature / ℃ 480 500 450 480 480 480 450 First hot rolling preheating time / h 2 1 1.5 2 2 2 1.5 Thickness after first hot rolling / mm 6 5 8 6 6 6 8 Thickness after cold rolling / mm 3 2 4 3 3 3 4 First annealing temperature / ℃ 350 360 300 330 350 350 300 First annealing time / h 3 1 3 3 3 3 3 Second hot rolling preheating temperature / ℃ 480 475 485 480 480 480 Cold Rolling Second hot rolling preheating time / min 30 20 40 30 30 30 Cold Rolling Thickness after the second hot rolling / mm 1.5 1 2 1.5 1.5 1.5 2 Second annealing temperature / ℃ 460 455 465 460 460 460 465 Second annealing time / min 30 20 60 30 30 30 60

[0088] The Al-Mn aluminum alloys obtained in Examples 1 to 7 were tested using the above-mentioned testing method. The distribution of the AlMnSiFe dispersed phase in the Al-Mn aluminum alloy provided in Example 1 is shown in FIG. Figure 1 As shown, Al x Cu y The distribution of nano-reinforced phase is shown in the figure Figure 2 As shown, from Figure 1-2It can be seen that in Al-Mn aluminum alloys, AlMnSiFe dispersed phase and Al x Cu y The nano-reinforced phase is evenly distributed and Al x Cu y The phase size of the nano-reinforced phase is ≤70nm, and the phase size of the AlMnFeSi dispersed phase is ≤650nm.

[0089] The specific test results of Examples 1 to 7 are shown in Table 3.

[0090] Table 3

[0091]

[0092] From Tables 1 to 3, we can see the following points:

[0093] (1) It can be seen from Examples 1 to 7 that the Al-Mn aluminum alloy provided by the present invention controls the solid solubility of Mn to ≤ 0.4wt% and makes the Al-Mn aluminum alloy contain Al x Cu y Nano-strengthening phase and AlMnFeSi dispersed phase, Al x Cu y When the atomic number ratio x:y of Al and Cu elements in the nano-strengthening phase is in the range of 2:1 to 4:1, the yield strength Rp0.2 of the final Al-Mn aluminum alloy is above 60MPa, and the elongation A50 is above 15%, which can have both excellent strength and plasticity.

[0094] (2) It can be seen from the comparison of the comprehensive examples, especially the comparison of Example 1 and Example 5, that when the Mg content is higher than 0.6%, part of the Mg element will be dissolved in the matrix during the entire material processing process. It is difficult to completely dissolve the Mg element in the AlCuMg phase in the matrix during the secondary annealing process, resulting in a large amount of residual AlCuMg phase and Al x Cu y The distribution density of nano-strengthening phase is reduced to 1.2%, and the strengthening effect is reduced; In summary, Al x Cu y The area proportion of the nano-strengthening phase is controlled to be above 1.2%, which has a better strengthening effect and a higher yield strength of the aluminum alloy;

[0095] (3) It can be seen from the comparison of the comprehensive embodiments, especially the comparison between Embodiment 1 and Embodiment 6, that in Embodiment 6, no Ti element is added, and the final average grain size is as high as 24.5 μm, and the yield strength of the aluminum alloy is 65 MPa, which is lower than the strength level of Embodiment 1. The present invention is more conducive to obtaining high strength by refining the grains, and the 0.01% to 0.1% Ti element in the present invention mainly plays a role in refining the grains.

[0096] (4) Comprehensive comparison of the embodiments, especially the comparison between Embodiment 3 and Embodiment 7, shows that the preheating in Embodiment 3 before the second hot rolling can be coordinated with the second annealing to effectively dissolve the Mg element in the AlMgCu phase back into the Al matrix, thereby precipitating smaller Al x Cu y Nano-strengthening phase. In Example 7, the second hot rolling was replaced by cold rolling, which resulted in the precipitation of Al x Cu y The area ratio of the nano-reinforced phase is reduced to 1.1%, which ultimately leads to a significant decrease in yield strength compared to Example 3.

[0097] Comparative Example 1

[0098] Comparative Example 1 is basically the same as Example 1, except that the Mg content in the Al-Mn aluminum alloy is 0.2wt%, the average grain size of the Al-Mn aluminum alloy is 13.5μm, and the Al x Cu y The nano-strengthening phase size is ≤70nm, the phase area accounts for 0.6%, the AlMnFeSi dispersed phase size is ≤650nm, the phase area accounts for 2.1%, the solid solubility of Mn element is 0.3wt%, and the yield strength Rp 0.2 is 54MPa, elongation A 50 It is 24%.

[0099] When the Mg content in Comparative Example 1 is too low, the AlCuMg phase is affected, which leads to the Al x Cu y The area ratio of the nano-strengthening phase is severely reduced, and the yield strength of the aluminum alloy finally obtained is relatively low.

[0100] Comparative Example 2

[0101] Comparative Example 2 is basically the same as Example 1, except that the Cu content in the Al-Mn aluminum alloy is 1.5wt%, the average grain size of the Al-Mn aluminum alloy is 12.6μm, and the Al x Cu y The nano-strengthening phase size is ≤70nm, the phase area accounts for 1.7%, the AlMnFeSi dispersed phase size is ≤650nm, the phase area accounts for 2.3%, the solid solubility of Mn element is 0.3wt%, and the yield strength Rp 0.2 is 75MPa, elongation A 50 It is 14%.

[0102] When the Cu content in Comparative Example 2 is too high, the plasticity of the aluminum alloy will be reduced and the elongation will be significantly reduced.

[0103] Comparative Example 3

[0104] Comparative Example 3 is basically the same as Example 1, except that the Cu content in the Al-Mn aluminum alloy is 0.3wt%, the average grain size of the Al-Mn aluminum alloy is 13.6μm, and there is no Al x Cu y Nano-strengthening phase, AlMnFeSi dispersed phase size ≤650nm, phase area accounts for 2.2%, the solid solubility of Mn element is 0.3wt%, yield strength Rp 0.2 is 51MPa, elongation A 50 It is 22%.

[0105] When the Cu content in Comparative Example 3 is too low, it is difficult to generate Al in the subsequent annealing process. x Cu y Nano-reinforced phase results in no significant strengthening improvement and insufficient yield strength.

[0106] Comparative Example 4

[0107] Comparative Example 4 is basically the same as Example 1, except that the Mn content in the Al-Mn aluminum alloy is 0.5wt%, the average grain size of the Al-Mn aluminum alloy is 16.3μm, and the Al x Cu y Nano-strengthening phase size ≤70nm, phase area 1.5%, AlMnFeSi dispersed phase size ≤650nm, phase area 0.7%, Mn element solubility 0.1wt%, yield strength Rp 0.2 is 49MPa, elongation A 50 It is 24%.

[0108] It can be seen from Comparative Example 4 that when the Mn element content is too low, the solid solution strengthening effect is small, and it is difficult to ensure that sufficient submicron-sized AlMnFeSi dispersed phases are precipitated during the subsequent heat treatment, resulting in insufficient yield strength.

[0109] Comparative Example 5

[0110] Comparative Example 5 is basically the same as Example 1, except that when preparing the Al-Mn aluminum alloy, the homogenization temperature is 480°C, and the average grain size of the Al-Mn aluminum alloy is 15.6 μm. x Cu y The phase size of nano-strengthening is ≤70nm, the phase area accounts for 1.1%, the AlMnFeSi dispersed phase size is ≤650nm, the phase area accounts for 1.1%, the solid solubility of Mn element is 0.7wt%, and the yield strength Rp 0.2 is 72MPa, elongation A 50 It is 13%.

[0111] Referring to Comparative Example 5, the homogenization temperature in the present invention has a great influence on the solid solubility of Mn, wherein too low a homogenization temperature will cause a large amount of Mn element to be dissolved in the matrix. Although it will improve the strength of the material to a certain extent, it will have a great negative impact on the elongation of the material. However, at the same time, the homogenization temperature should not exceed 600°C, otherwise the homogenization temperature will be close to the melting point of the aluminum alloy, which will make it impossible to process.

[0112] Comparative Example 6

[0113] Comparative Example 6 is basically the same as Example 1, except that when preparing the Al-Mn aluminum alloy, the first annealing temperature is 280°C, and the average grain size of the Al-Mn aluminum alloy is 14.4 μm. x Cu y Nano-strengthening phase size ≤70nm, phase area 0.7%, AlMnFeSi dispersed phase size ≤650nm, phase area 2.1%, Mn element solubility 0.3wt%, yield strength Rp 0.2 is 57MPa, elongation A 50 It is 22%.

[0114] In Comparative Example 6, if the temperature of the first annealing is too low, less submicron-sized AlMgCu phase will be precipitated, which will lead to Al x Cu y The area proportion of the nano-reinforced phase is insufficient, and the yield strength is correspondingly low.

[0115] Comparative Example 7

[0116] Comparative Example 7 is basically the same as Example 1, except that when preparing the Al-Mn aluminum alloy, the second annealing temperature is 400°C, and the average grain size of the Al-Mn aluminum alloy is 12.6 μm. x Cu y The phase size of nano-strengthening is ≤70nm, the phase area accounts for 0.5%, the AlMnFeSi dispersed phase size is ≤650nm, the phase area accounts for 2.1%, the solid solubility of Mn element is 0.3wt%, and the yield strength Rp 0.2 is 52MPa, elongation A 50 is 21%.

[0117] In Comparative Example 7, the temperature of the second annealing was too low, resulting in less Mg solid solution and Al x Cu y The amount of nano-reinforced phase decreases, and the yield strength is correspondingly lower.

[0118] Comparative Example 8

[0119] Comparative Example 8 is basically the same as Example 1, except that when preparing the Al-Mn aluminum alloy, the first annealing temperature is 380°C, the average grain size of the Al-Mn aluminum alloy obtained is 16.3 μm, and the alloy contains coarse Al x Cu y Strengthening phase and AlMnFeSi dispersed phase, among which Al with phase size ≤70nm x Cu y The nano-strengthening phase accounts for 1.1% of the area, but the phase with a phase size of >70nm accounts for 0.5%. The AlMnFeSi dispersed phase with a phase size of ≤650nm accounts for 1.7%, but the phase with a phase size of >650nm accounts for 0.5%. The solid solubility of Mn element is 0.3wt%, and the yield strength Rp 0.2 is 54MPa, elongation A 50 It is 22%.

[0120] Comparative Example 9

[0121] Comparative Example 9 is basically the same as Example 1, except that when preparing the Al-Mn aluminum alloy, the second annealing temperature is 480°C, the average grain size of the Al-Mn aluminum alloy obtained is 16.1 μm, and the alloy contains coarse Al x Cu y Strengthening phase and AlMnFeSi dispersed phase, among which Al with phase size ≤70nm x Cu y The nano-strengthening phase accounts for 1.3% of the area, but the phase with a phase size of >70nm accounts for 0.5%. The AlMnFeSi dispersed phase with a phase size of ≤650nm accounts for 1.4%, but the phase with a phase size of >650nm accounts for 0.6%. The solid solubility of Mn element is 0.3wt%, and the yield strength Rp 0.2 is 54MPa, elongation A 50 It is 23%.

[0122] Combining Example 1, Comparative Example 8 and Comparative Example 9, it can be seen that in Example 1, the temperatures of the first annealing and the second annealing are controlled within a reasonable range, and Al x Cu y The size of the nano-reinforced phase is controlled to be almost ≤70nm, and the size of the AlMnFeSi phase is controlled to be almost ≤650nm. Finally, the yield strength Rp0.2 of Example 1 is 71MPa, and the elongation A50 is 19%, and it has excellent strength and plasticity. However, the first annealing temperature in Comparative Example 8 is 380℃, and the second annealing temperature in Comparative Example 9 is 480℃, which leads to the precipitated AlxCuy nano-reinforced phase and AlMnFeSi phase having larger sizes, and finally the yield strength is only 52 and 54MPa, respectively. This shows that the present invention reduces the Al x Cuy The size of the nano-strengthening phase is controlled to be almost ≤70nm, and the size of the AlMnFeSi phase is controlled to be almost ≤650nm, so that the aluminum alloy has a higher yield strength.

[0123] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An Al-Mn aluminum alloy, It is characterized in that The Al-Mn aluminum alloy contains Al x Cu y Nano-strengthening phase and AlMnFeSi dispersed phase; The solid solubility of Mn in the Al-Mn alloy is ≤0.4wt%; The Al x Cu y The atomic number ratio x:y of Al and Cu elements in the nano-strengthened phase is 2:1 to 4:

1.

2. The Al-Mn aluminum alloy according to claim 1, It is characterized in that The Al x Cu y The phase size of the nano-strengthening phase is ≤70nm, Al x Cu y The area proportion of the nano-reinforced phase is ≥1.1%; Preferably, the composition of the Al-Mn aluminum alloy includes, by mass percentage, 0.3-0.6% Mg and 0.5-1.0% Cu.

3. The Al-Mn aluminum alloy according to claim 1 or 2, It is characterized in that The phase size of the AlMnFeSi dispersed phase is ≤650nm, and the area proportion of the AlMnFeSi dispersed phase is ≥1.4%. Preferably, the composition of the Al-Mn aluminum alloy includes, by mass fraction: 0.6-1.5% Mn, 0.2-0.5% Fe and 0.5-1.0% Si; Preferably, the content of Fe+Mn in the Al-Mn aluminum alloy is ≤1.9%.

4. The Al-Mn aluminum alloy according to any one of claims 1 to 3, It is characterized in that The average grain size of the Al-Mn aluminum alloy is ≤24 μm; Preferably, the Al—Mn aluminum alloy further includes 0.01 to 0.1% Ti.

5. A method for preparing the Al-Mn aluminum alloy according to any one of claims 1 to 4, It is characterized in that The preparation method comprises the following steps: (1) preparing ingredients according to the components and weight percentages to obtain a mixed material; (2) melting and casting the mixed material prepared in step (1) in sequence to obtain an aluminum ingot; (3) homogenizing the aluminum ingot obtained in step (2) at 500-600° C. for 8-15 h to precipitate an AlMnSiFe phase, thereby obtaining a homogenized sample; (4) The homogenized sample in step (3) is subjected to first hot rolling, cold rolling, first annealing, second hot rolling and second annealing in sequence to form Al x Cu y Nano-strengthening phase is obtained to obtain the Al-Mn aluminum alloy.

6. The preparation method according to claim 5, It is characterized in that The first annealing temperature is 300-360°C and the time is 1-3h; Preferably, the second annealing is performed at a temperature of 455-465° C. and for a time of 20-60 min.

7. The preparation method according to claim 5 or 6, It is characterized in that The preheating temperature of the first hot rolling is 450-500°C, and the thickness after the first hot rolling is 5-8 mm; Preferably, the preheating time of the first hot rolling is 1 to 2 hours.

8. The preparation method according to any one of claims 5 to 7, It is characterized in that The thickness after cold rolling is 2 to 4 mm.

9. The preparation method according to any one of claims 5 to 8, It is characterized in that The preheating temperature of the second hot rolling is 475-485°C, and the thickness after the second hot rolling is 1-2 mm; Preferably, the preheating time of the second hot rolling is 20 to 40 minutes.

10. Use of the Al-Mn aluminum alloy according to any one of claims 1 to 4 in the field of heat transmission.

Citation Information

Cited By

  • High-temperature-creep-resistant aluminum alloy and preparation method thereof

    CN121023312A

  • A high-temperature creep-resistant aluminum alloy and a preparation method thereof

    CN121023312B